Microfluidic concurrent assessment of red blood cell adhesion and microcapillary occlusion: potential hemorheological biomarkers in sickle cell disease - Man, Yuncheng; Wu, Douglas H; An, Ran; Wei, Peiran; Monchamp, Karamoja; Goreke, Utku; Sekyonda, Zoe; Wulftange, William J; Federici, Chiara; Bode, Allison; Nayak, Lalitha V; Little, Jane A; et al. (Sensors & diagnostics, 2023)
Deformability and non-adherence are two fundamental functional properties of red blood cells (RBCs), which allow them to move unimpeded through the microvasculature. In sickle cell disease (SCD), polymerization of abnormal sickle hemoglobin leads to decreased deformability and increased membrane adhesiveness in RBCs. This contributes to abnormal blood vessel occlusion, which is central to the underlying pathophysiology. RBC deformability and adhesiveness are, therefore key hemorheological biomarkers in characterizing disease states as well as in evaluating novel therapeutics. To date, these important interrelated biomarkers have been assessed in distinct laboratory assays, without integration or concurrent assessment in vitro . To this end, we present a novel microfluidic assay in which laminin (LN, a sub-endothelial matrix protein that mimics microvascular damage and extracellular matrix exposure)-functionalized microcapillaries ranging from 20 μm to 4 μm are embedded in microchannels, for simultaneous assessment of microcapillary occlusion mediated by RBC deformability and vascular cellular adhesion mediated by pathologic RBC membrane changes. We show that RBC adhesion to LN or microcapillary occlusion can be associated with markers for intravascular hemolysis or iron overload in SCD. Following allogeneic hematopoietic stem cell transplant (HSCT), which is a curative therapy, in a single subject with SCD, RBC-mediated microcapillary occlusion fell into the healthy range, but RBC adhesion to LN, albeit significantly decreased, remained outside the healthy range. Our findings demonstrate the potential of this bifunctional assay, in both monitoring the clinical course and supplementing clinical observations with comprehensive evaluation of two functional hemorheological properties. A microfluidic assay integrated with capillary network-inspired microcapillary arrays and endothelial-associated protein functionalization enables concurrent assessment of red blood cell adhesion and microcapillary occlusion.